(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article examines the effects of the airline industry in sustainable tourism in Uzbekistan by focusing on some methods that need to be applied in Uzbekistan Airways. This research highlights the impacts of modernization and digital improvements in optimizing operational efficiency, passenger experience and its global market strength, by studying comparisons with Qatar Airways and Turkish Airlines identifying key areas for improvements such as in network connectivity, service quality staff professionalism, partnerships with tourism stakeholders. Overall, the article below gives some strategic development recommendations that plays crucial role in sustainable tourism growth of Uzbekistan and increase country’s position as a key travel destination around the world.